Las mujeres de los hogares populares urbanos y el manejo cotidiano del espacio - Salazar Cruz, C.
tbls.
pp. 267-292
Keywords: Trabajadoras; Vida Cotidiana; Trabajadores Domesticos; Sociologia Urbana; Mexico, D.f.; Hogares